rút gọn biểu thức: a.(a+b)^3 -(a-b)^3 -2b^3
b.(6x+1)^2+(6x-1)^2-2(1+6x)(6x-1)
rút gọn biểu thức
a)(x+y)^2-(x-y)^2
b)2.(x+y).(x-y)+(x+y)^2+(x-y)^2
c)(x+3).(x^2-3x+9)-(54+x^3)
d)(2x+y).(4x^2-2xy+y^2)-(2x-y)
e)(6x+1)^2+(6x-1)^2-2.(6x+1).(6x-1)
f)(a-b)^3-(a+b)^3+2b^3
câu c (x+3)(x^2-3x+9)-(54+x^3)=x^3+27-54-x^3
=27
Rút gọn biểu thức:
a, (6x+1)^2+(6x-1)^2-2(1+6x)(6x-1)
b, 3(2^2+1)(2^4+1)(2^8+1)(2^16+1)
\(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)
\(=\left(6x+1-6x+1\right)^2\)
\(=2^2=4\)
\(3\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(=\left(2^4-1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(=\left(2^8-1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)
\(=\left(2^{16}-1\right)\left(2^{16}+1\right)\)
\(=2^{32}-1\)
Rút gọn biểu thức:
a) (6x+1)^2+(6x-1)^2-2(1+6x)(6x-1).
b) 3(2^2+1)(2^4+1)(2^8+1)(2^16+1).
a) \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)
\(=\left(6x+1\right)\left(6x+1\right)+\left(6x-1\right)\left(6x-1\right)-2\left(1+6x\right)\left(6x-1\right)\)
\(=\left(6x+1\right)\left(6x+1\right)+\left(6x-1\right)\left[\left(6x-1\right)-2\left(1+6x\right)\right]\)
\(=\left(6x+1\right)\left(6x+1\right)+\left(6x-1\right)\left(6x-1-2-12x\right)\)
\(=36x^2+12x+1+\left(6x-1\right)\left(-6x-3\right)\)
\(=36x^2+12x+1+\left(-36x^2-12x+3\right)\)
\(=36x^2+12x+1-36x^2-12x+3\)
\(=4\)
Bài 3: Rút gọn biểu thức:
a) (6x+1)2+(6x-1)2-2(1+6x)(6x-1); b) 3(22+1)(24+1)(28+1)(216+1); c) x(2x2-3)-x2(5x+1)+x2; d) 3x(x-2)-5x(1-x)-8(x2-3)
Bài 1: Tính:
a) x2(x-2x3); b) (x2+1)(5-x); c) (x-2)(x2+3x-4); d) (x-2)(x-x2+4); e) (x2-1)(x2+2x); f) (2x-1)(3x+2)(3-x)
Bài 2: Tính:
a) (x-2y)2; b) (2x2+3)3; c) (x-2)(x2+2x+4); d) (2x-1)3
Bài 3: Rút gọn biểu thức:
a) (6x+1)2+(6x-1)2-2(1+6x)(6x-1); b) 3(22+1)(24+1)(28+1)(216+1); c) x(2x2-3)-x2(5x+1)+x2; d) 3x(x-2)-5x(1-x)-8(x2-3)
Bài 4: Tính nhanh:
a) 1012; b) 97.103; c) 772+232+77.46; d) 1052-52; e) A= (x-y)(x2+xy+y2)+2y3 tại x= \(\dfrac{2}{3}\) và y= \(\dfrac{1}{3}\)
Bạn chú ý đăng lẻ câu hỏi! 1/
a/ \(=x^3-2x^5\)
b/\(=5x^2+5-x^3-x\)
c/ \(=x^3+3x^2-4x-2x^2-6x+8=x^3=x^2-10x+8\)
d/ \(=x^2-x^3+4x-2x+2x^2-8=3x^2-x^3+2x-8\)
e/ \(=x^4-x^2+2x^3-2x\)
f/ \(=\left(6x^2+x-2\right)\left(3-x\right)=17x^2+5x-6-6x^3\)
Rút gọn biểu thức:
a) (6x + 1)^2 + (6x-1)^2 - 2(1+6x)(6x-1)
b) 3(2^2 +1) (2^4 +1) (2^8 +1)(2^16 +1)
c) x(2x^2 - 3) -x^2 (5x +1) +x^2
d) 3x(x-2) - 5x(1-x) - 8(x^2 - 3)
a) \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)
\(=36x^2+12x+1+36x^2-12x+1-72x^2+2\)
\(=4\)
c) \(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)
\(=2x^3-3x-5x^3-x^2+x^2\)
\(=-3x^3-3x\)
d) \(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)
\(=3x^2-6x-5x+5x^2-8x^2+24\)
\(=-11x+24\)
rút gọn biểu thức
a.(6x+1)^2-(6x-1)-2(1+6x)(6x-1)
b . x(2x^2-3) -x^2(5x+1)+x^2
c.3(2^2+1)(2^4+1)(2^8+1)(2^16+1)
d.3x(x-2)-5x(1-x-8)(x^2-3)
Rút gọn biểu thức:
a) (2x + 1)2 + (2x - 1)2 - 2(x - 3)2
b) (x - 1)2 - (3x + 2)2
c) (6x + 1)2 + (6x - 1)2 - 2(1 + 6x) (6x - 1)
Rút gọn biểu thức:
a) (2x + 1)2 + (2x - 1)2 - 2(x - 3)2
b) (x - 1)2 - (3x + 2)2
c) (6x + 1)2 + (6x - 1)2 - 2(1 + 6x) (6x - 1)
a: \(\left(2x+1\right)^2+\left(2x-1\right)^2-2\left(x-3\right)^2\)
\(=4x^2+4x+1+4x^2-4x+1-2\left(x^2-6x+9\right)\)
\(=8x^2+2-2x^2+12x-18\)
\(=6x^2+12x-16\)
b: \(\left(x-1\right)^2-\left(3x+2\right)^2\)
\(=x^2-2x+1-9x^2-12x-4\)
\(=-8x^2-14x-3\)
c: \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(6x+1\right)\left(6x-1\right)\)
\(=\left(6x+1\right)^2-2\left(6x+1\right)\left(6x-1\right)+\left(6x-1\right)^2\)
\(=\left(6x+1-6x+1\right)^2=2^2=4\)